2018
DOI: 10.1213/ane.0000000000003310
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Major Adverse Postoperative Events and Myocardial Injury on Disability and Survival: A Planned Subanalysis of the ENIGMA-II Trial

Abstract: MACEs and MAPEs occur at similar frequencies and affect survival to a similar degree. All 3 types of postoperative troponin elevation in this analysis were associated, to varying degrees, with increased risk of death and disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 34 publications
1
29
0
2
Order By: Relevance
“…The increases in troponin I (n = 11, 13% of patients) found in our study were primarily subclinical values below the clinical cut‐off of 45 ng.l −1 for myocardial ischaemia used at our centre. Only four patients had values above the clinical cut‐off, which is markedly lower than what is found in other studies, where it ranged from 18% to 19% . The VISION trial used a peak increase in troponin T well below the clinical cut‐off, and found an incidence of 11.6%, which is similar to our findings.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The increases in troponin I (n = 11, 13% of patients) found in our study were primarily subclinical values below the clinical cut‐off of 45 ng.l −1 for myocardial ischaemia used at our centre. Only four patients had values above the clinical cut‐off, which is markedly lower than what is found in other studies, where it ranged from 18% to 19% . The VISION trial used a peak increase in troponin T well below the clinical cut‐off, and found an incidence of 11.6%, which is similar to our findings.…”
Section: Discussionsupporting
confidence: 74%
“…There may be an association between postoperative hypoxaemia and myocardial ischaemia. The study by Devereaux et al and subsequent studies have shown that an isolated troponin increase in the postoperative period is not only associated with increased 30‐day mortality and risk of ischaemic events, but also influences long‐term outcomes. Hypoxaemia is by definition reduced availability of oxygen in the tissues, which could lead to subclinical ischaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, because myocardial infarction was defined as a clinical diagnosis made by a cardiologist, the incidence of myocardial infarction may have been higher when it retrospectively would have been based on the 4 th universal definition (Thygesen et al 2018), as previously shown. (Beattie et al 2018;Devereaux et al 2011;van Waes et al 2016) Finally, only documented consultations by the anesthesiologist were recorded as consultation, which potentially explains why 37% of the patients did not receive a consultation. As part of the local protocol, anesthesiologists determined whether consultation was necessary based on clinical course reported in the electronic medical files and consultation of treating physicians by phone.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, troponin elevation has also been related to other disease entities including stroke, sepsis and pulmonary embolism. (Akkermans et al 2019;Beattie et al 2018;Noordzij et al 2015;van Waes et al 2016) We hypothesized a more general approach to assess postoperative troponin elevation, rather than an approach focusing on cardiac etiology, would be beneficial. As a result, in October 2016 we implemented routine postoperative consultations by a dedicated anesthesia team in patients detected with an elevated troponin in the surveillance program.…”
Section: Introductionmentioning
confidence: 99%
“…12 Of note, both studies suggested decreases in both mortality and length of stay that were much greater than many specific therapeutic interventions. 4,5 These two studies also highlight the need to consider a range of outcomes. Mortality is relatively uncommon, but measurable and more frequent events include medical emergency response calls, 13 hypotension, 4 length of stay, 11,12 and events after hospital discharge.…”
mentioning
confidence: 99%